Measurement of D-dimer in cerebrospinal fluid using a luminescent oxygen channeling immunoassay - Kohlhase, Konstantin; Schaefer, Jan Hendrik; Miesbach, Wolfgang; Hintereder, Gudrun; Kirchmayr, Konstantin; Zwinge, Birga; Yalachkov, Yavor; Foerch, Christian; Schaller-Paule, Martin A. (Frontiers in Neurology, 2022)
Background: Measurement of D-dimer in cerebrospinal fluid (CSF) allows insight into coagulation system activation in the central nervous system and can be utilized to monitor intracranial hemorrhage as well as acute phase processes beyond hemostasis in inflammatory and neoplastic diseases. So far, the measurability of D-dimer in low and very low concentrations in CSF was limited in conventional immunoassays. Novel high-sensitivity chemiluminescent immunoassays such as the Luminescent Oxygen Channeling Immunoassay (LOCI®) are getting increasingly available but have not been validated in CSF. Aim of this study was to investigate the accuracy and linearity of the LOCI® in assessing D-dimer in CSF. Methods: INNOVANCE LOCI hs D-dimer reagent cartridge was used for the measurement of D-dimer in CSF of patients with different neurological diseases. For the evaluation of linearity, dilution series were performed in a pooled CSF sample with determination of intraassay precision (CV – coefficient of variation) in 3 individual samples with 20 replicates. Furthermore, D-dimer concentrations measured by LOCI® were compared with the respective results of a routinely available clinical latex-enhanced immunoassay (HemosiIL D-Dimer HS 500). Results: Linear regression analysis of the LOCI® method revealed a r2 of 1.00 (p < 0.001) with a regression coefficient B of 1.012 ± 0.003 (CI: 1.005–1.019, p < 0.001) and an intercept of -1.475 ± 1.309 (CI: -4.493 – 1.543); intraassay CV was in median 0.69% (range: 0.68 – 0.75). In total 185 CSF samples were measured by LOCI® technology showing a mean concentration of 204.84 ± 2214.93 ng/mL with a mean deviation of 682 ± 1170% on average and a maximum deviation of 6033% compared with those measured by the latex enhanced immunoassay; the maximum deviation was found at low concentrations. Conclusions: D-dimer in CSF of patients with neurological disease can be reliably measured by the LOCI® method with high linearity and accuracy even at very low concentrations.